Parental involvement as a determinant of academic performance of gifted underachieving students in Akinyele Local Government Area of Oyo State (2013)
Extensive research has shown that the underachievement of capable children is an area of concern for many parents and educators. This study investigated the role of parents in enhancing academic performance of underachieving students in Akinyele Local Government Area of Oyo State, Nigeria. The study adopted a descriptive survey design. A sample size of one hundred (100) was randomly selected using stratified random sampling technique with forty nine (49) males and fifty one (51) females. Majority of the subjects used fell within the ages of seventeen (17) and nineteen (19). A structured questionnaire and verbal interview method were used to collect data from the selected subjects. Three hypotheses were tested using percentiles and normal distribution as statistical tools for data analysis. The findings showed that there was no significant difference between the academic performance of underachieving students with single parent and those with both parents (Crit – t = 1.96, Cal. t = 0.798, df = 98, P > 0.05 level of significance). The findings also showed that there was no significant difference between the academic performance of underachieving students whose parents live in the urban area and those whose parents live in rural area (Crit – t = 1.96, Cal. t = 0.186, df = 98, P > 0.05 level of significance). Finally, the result also indicated that there was no significant difference between the academic performance of underachieving students whose parents are of low socio-economic status and those whose parents are of high socio-economic status (Crit – t = 1.96, Cal.t = 0.135, df = 98, P > 0.05 level of significance).